1/2(8x - 6) = x - 12

What does x equal?

11 answers

To solve the equation \( \frac{1}{2}(8x - 6) = x - 12 \), we will follow these steps:

  1. Distribute \( \frac{1}{2} \) to both terms inside the parentheses:

\[ \frac{1}{2} \cdot 8x - \frac{1}{2} \cdot 6 = 4x - 3 \]

  1. So, the equation now looks like this:

\[ 4x - 3 = x - 12 \]

  1. Next, we will isolate \( x \). First, subtract \( x \) from both sides:

\[ 4x - x - 3 = -12 \]

This simplifies to:

\[ 3x - 3 = -12 \]

  1. Now, add \( 3 \) to both sides:

\[ 3x = -12 + 3 \]

This simplifies to:

\[ 3x = -9 \]

  1. Finally, divide both sides by \( 3 \):

\[ x = \frac{-9}{3} = -3 \]

Thus, the value of \( x \) is

\[ \boxed{-3} \]

4q - 8
+ 2q

To simplify the expression \(4q - 8 + 2q\), follow these steps:

  1. Combine the like terms (the terms with \(q\)): \[ 4q + 2q = 6q \]

  2. Now, rewrite the expression with the combined terms: \[ 6q - 8 \]

So, the simplified expression is:

\[ \boxed{6q - 8} \]

-2q - 5
+ 2q

To simplify the expression \(-2q - 5 + 2q\), follow these steps:

  1. Combine the like terms (the terms with \(q\)): \[ -2q + 2q = 0 \]

  2. Now, rewrite the expression with the combined terms: \[ 0 - 5 \]

  3. This simplifies to: \[ -5 \]

So, the simplified expression is:

\[ \boxed{-5} \]

5h - 6
+ 6

To simplify the expression \(5h - 6 + 6\), follow these steps:

  1. Combine the constant terms: \[ -6 + 6 = 0 \]

  2. Now, rewrite the expression with the combined terms: \[ 5h + 0 \]

  3. Since adding zero does not change the value, the expression simplifies to: \[ 5h \]

So, the simplified expression is:

\[ \boxed{5h} \]

-5
+ 6

To simplify the expression \(-5 + 6\), simply perform the addition:

\[ -5 + 6 = 1 \]

So, the simplified result is:

\[ \boxed{1} \]

5h = 1
What does h equal?

To solve the equation \(5h = 1\) for \(h\), you need to isolate \(h\). You can do this by dividing both sides of the equation by 5:

\[ h = \frac{1}{5} \]

Thus, the value of \(h\) is

\[ \boxed{\frac{1}{5}} \]